History of Tree Growth Declines Recorded in Old Trees at Two Sacred Sites in Northern China - Li, Yan; Zhang, Qi-Bin (Frontiers in Plant Science, 2017)
Old forests are an important component in sacred sites, yet they are at risk of growth decline from ongoing global warming and increased human activities. Growth decline, characterized by chronic loss of tree vigor, is not a recent phenomenon. Knowledge of past occurrence of declines is useful for preparing conservation plans because it helps understand if present day forests are outside the natural range of variation in tree health. We report a dendroecological study of growth decline events in the past two centuries at two sacred sites, Hengshan and Wutaishan, in Shanxi province of northern China. Tree rings collected at both sites show distinct periods of declining growth evident as narrow rings. These occurred in the 1830s in both sites, in the 1920s in Wutaishan and in the 2000s in Hengshan. By comparing the pattern of grow declines at the two sites, we hypothesize that resistance of tree growth to external disturbances is forest size dependent, and increased human activity might be a factor additional to climatic droughts in causing the recent strong growth decline at Hengshan Park. Despite these past declines, the forests at both sites have high resilience to disturbances as evidenced by the ability of trees to recover their growth rates to levels comparable to the pre-decline period. Managers should consider reducing fragmentation and restoring natural habitat of old forests, especially in areas on dry sites.